Collective wellbeing and posttraumatic growth during COVID-19: how positive psychology can help families, schools, workplaces and marginalized communities. Issue 6 (2nd November 2022) - Waters, Lea; Cameron, Kim; Nelson-Coffey, S. Katherine; Crone, Damien L.; Kern, Margaret L.; Lomas, Tim; Oades, Lindsay; Owens, Rhea L.; Pawelski, James O.; Rashid, Tayyab; Warren, Meg A.; White, Mathew A.; et al.
ABSTRACT: Positive psychology approaches have been shown to play a vital role in protecting mental health in times of challenge and are, therefore, important to include when studying the psychological outcomes of COVID-19. While existing research has focused on individual psychological health, this paper focuses on collective wellbeing and collective posttraumatic growth, with the aim of more clearly identifying the positive experiences and potential for positive growth for key institutions in our society during the pandemic. A range of positive psychology interventions for families, schools, workplaces, and clinical psychology are presented. The paper then considers how three broad-reaching phenomena existing in our wider society (i.e., arts and culture, eco-connection, and wellbeing literacy) can be used to boost collective wellbeing. A positive systems approach to understand civilian responses to the pandemic together with an examination of the role that positive psychology can play in supporting marginalized groups are also discussed.